2005
DOI: 10.1179/joc.2005.17.5.502
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Telithromycin Against Multi-Drug ResistantStreptococcus pneumoniaeand Molecular Characterization of Macrolide and Tetracycline Resistance Determinants

Abstract: The antistreptococcal activity of telithromycin and 11 different comparators was evaluated in 26 multi-drug resistant (MDR) Streptococcus pneumoniae strains collected during 2002-2003 as part of the ongoing PROTEKT (Prospective Resistant Organism Tracking and Epidemiology for the Ketolide Telithromycin) Italian Surveillance Program. The strains were characterized for their susceptibility to antibiotics both at the phenotypic and genotypic levels; furthermore, the association of erm(B), mef(A) class and tet(M) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Ketolides are active against pneumococci that have a macrolide efflux pump (9). Telithromycin is active against macrolide-resistant pneumococci that contain either the methylase or the efflux mechanism of resistance (8,9). However, the greater frequency of liver damage with telithromycin than with other macrolides resulted in its withdrawal of approval for two of three indications after postmarketing reports (11,28).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ketolides are active against pneumococci that have a macrolide efflux pump (9). Telithromycin is active against macrolide-resistant pneumococci that contain either the methylase or the efflux mechanism of resistance (8,9). However, the greater frequency of liver damage with telithromycin than with other macrolides resulted in its withdrawal of approval for two of three indications after postmarketing reports (11,28).…”
Section: Discussionmentioning
confidence: 99%
“…Antibacterial resistance, and macrolide resistance in S. pneumoniae in particular, is increasing worldwide, and this presents treatment challenges to physicians (8,27). Ketolides are active against pneumococci that have a macrolide efflux pump (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The entire element carrying mef (E) was amplified by long PCR using MS146/MS147 primers designed on the nucleotide sequence of mega ends (Cascone et al , 2005). Sequence analysis demonstrated that mega of strain 3C30 is 5388 bp long and is 100% identical to the mega element described previously in S. salivarius (GenBank accession no. )…”
Section: Resultsmentioning
confidence: 99%
“…Genomic DNA was extracted from all bacterial cultures as previously described [8] and used as a template for amplification. PCR experiments were carried out by established procedures following the reported conditions for the use of individual primer pairs and following procedures previously published [9]. PCR products were analysed by electrophoresis on 1% agarose gels (Sigma-Aldrich, St Louis, MO).…”
Section: Identification Of Resistance Genes and Resistance Cassettesmentioning
confidence: 99%